Território e subjetividade: os desafios da cidadania no cotidiano de usuários de serviços de saúde mental - Lucas Herique Braga (2013)
The Psychiatric Reform Movement is responsible, in Brazil, for the labor reformulation in the mental health field. Whereof this new care paradigm, a practice which consideres the subject inserted in a wider context than the one offered by the health attention in the hospitals has been thought. The work that has been developed intend to encompass these subjects life production, considering each ones uniqueness of the interactions in the different spaces of sociability whereby they move along. The new care modality created the need of an outbreak of new services, whose work premise is exactly the promotion of the subjects autonomy, allowing life, at the same time, to become more complex as the contacts with the territory are established. However, the simple creation of the services by the State doesnt imply the immediate overcome of the psychiatric hospitals model, which still makes itself present and generate new ways of segregation and stigmatization regarding the users of mental health services. Thus, concepts like space, territory and city are crucial to think about this new labor modality, and they are analyzed in this article according the authors who dedicated themselves to think about this question. These theories served as the basis for an empiric research, accomplished with the users of substitute services to the psychiatric hospital, which compose the Belo Horizontes Psychosocial Attention Network. Five subjects, among the Therapeutic Residential Servicess residents and Companionship Centers users of a municipalitys regional, participated in the research. Participating observations of the subjects everyday were achieved, trying to identify how their relationships with the territory and the services which assist them are stablished. Through the acquired data, a critical analysis of the observed points was made, seeking to contribute with the new practices in mental health preconized by the Psychiatric Reform.